2016
DOI: 10.1037/emo0000122
|View full text |Cite
|
Sign up to set email alerts
|

Do losses loom larger for children than adults?

Abstract: The large impact of loss of reward on behavior has been well documented in adult populations. However, whether responsiveness to loss relative to gain is similarly elevated in child versus adult populations remains unclear. It is also unclear whether relations between incentive behaviors and self-reported reward/punishment sensitivity are similar within different developmental stages. To investigate these questions, 7–10-year-old children (N=70) and young adults (N=70) completed the Behavioral Inhibition Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Considering the “adolescent triadic model of motivated behavior”, our results support the notion that adolescence is a phase characterized by a greater dominance of the reward compared to the harm-avoidant system ( Ernst et al, 2006 ). Moreover, our findings are corroborated by imaging and behavioral studies demonstrating a lower sensitivity to punishment and negative feedback stimuli in adolescence (e.g., Humphreys et al, 2016 ; Luking et al, 2016 ; van den Bos et al, 2012 ). Similar to our findings, a longitudinal study demonstrated a higher fP3 amplitude after punishment (vs. rewards) in children, which the authors interpreted as greater neural sensitivity to punishment in this age group ( Harms et al, 2014 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Considering the “adolescent triadic model of motivated behavior”, our results support the notion that adolescence is a phase characterized by a greater dominance of the reward compared to the harm-avoidant system ( Ernst et al, 2006 ). Moreover, our findings are corroborated by imaging and behavioral studies demonstrating a lower sensitivity to punishment and negative feedback stimuli in adolescence (e.g., Humphreys et al, 2016 ; Luking et al, 2016 ; van den Bos et al, 2012 ). Similar to our findings, a longitudinal study demonstrated a higher fP3 amplitude after punishment (vs. rewards) in children, which the authors interpreted as greater neural sensitivity to punishment in this age group ( Harms et al, 2014 ).…”
Section: Discussionsupporting
confidence: 84%
“…In regard of the BAS scales, we focused only on the BAS drive scale to restrict further the number of analyses. This decision was built on the rationale that previous research in developmental samples (1) links between the BAS drive scale and incentive processing ( Luking et al, 2016 ), and (2) better psychometric properties for the BAS drive scale based on confirmatory factor analyses ( Pagliaccio et al, 2016 ; Vervoort et al, 2019 ) and results on internal consistency (Cronbach's alpha of BAS drive = .86, BAS fun = .57, BAS reward = .72, Vervoort et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Only one investigation has directly tested the relationship between DD and food reward using behavioural paradigms [32]. Using a modified probabilistic incentive-learning task in which children were rewarded with candy (Skittles or M&Ms), depressive symptoms were found to be unrelated to response bias in food reward [33]. These findings complement results from sugar taste tests in which depressed and nondepressed adults responded similarly in terms of pleasure ratings for increasingly sweeter sucrose solutions [3436].…”
Section: Resultsmentioning
confidence: 99%
“…This might be the reason why valence is often implemented between subjects in the developmental literature. In contrast to the former adult studies, this literature consistently indicates that children perform better during learning in negative-blank as compared with positive-blank conditions ( Barringer & Gholson, 1979 ; Curry, 1960 ; Meyer & Offenbach, 1962 ; Meyer & Seidman, 1960 , 1961 ; Penney, 1967 ; Penney & Lupton, 1961 ; Ratliff & Tindall, 1970 ; Spence, 1966b ; Tindall & Ratliff, 1974 ; see also Luking, Pagliaccio, Luby, & Barch, 2016 ). With respect to the end result of learning, three studies reported that learned materials were better maintained during extinction if they had been learned in negative-blank as compared with positive-blank conditions ( Meyer & Seidman, 1960 , 1961 ; Ratliff & Tindall, 1970 ), whereas other studies did not report end result data.…”
mentioning
confidence: 86%